ANALISIS PERSEPSI RISIKO PADA TENAGA KESEHATAN DI FASILITAS KESEHATAN SAAT PANDEMI COVID-19: A LITERATURE REVIEW - Atthina Ayu Mustika (Jurnal Medika Hutama, 2022)
COVID-19 pandemic that spread throughout the world in a short time made health-care workers work harder as hundreds of millions of people were affected by the SARS-CoV-2 virus and more than four million people died from 2020 to 2021. The burden and risk of health workers is increasing when COVID-19 patients are crowded in health facility, compared to the workload and risks before the pandemic. Risk perception of health care workers affecting their mental and physical health is very important to accelerate the response to the pandemic. This study aims to review literatures that discusses the risk perception of health care workers in dealing with the diseases at health facilities. The research method uses structured library search steps in Pubmed and ProQuest databases with PICOS in the form of health care workers who treat COVID-19 patients in primary, secondary, tertiary health facilities, as well as their risk perceptions of COVID-19. Results of the study obtained seven articles that matched the researcher's criteria, where it is known that health care workers in health facilities, especially general practitioners who treat patients in COVID-19 services, lack of access to and training related to personal protective equipment, have a high risk perception of COVID-19. There are no articles showing differences in perceptions of health care workers in COVID-19 service rooms which are further detailed, such as differences in perceptions of health care workers in COVID-19 and non-COVID-19 inpatient rooms.